Unveiling the Silent Threat: The Escalation and Defence Against Antibiotic Resistance - Swapnesh Bhaduri (International Journal of Antibiotics, 2025)
The global challenge of antibiotic resistance presents a significant risk to public health, driven by multifaceted factors worldwide. This issue, akin to the impacts of climate change, requires concerted efforts at national and international levels to mitigate its consequences. Antibiotics have revolutionized modern medicine, enabling critical interventions like surgeries, transplants, and cancer treatments. However, without global collaboration, we face significant setbacks across medical, social, and economic domains. Initiatives to address resistance have resulted in numerous reports advocating for reduced antimicrobial prescribing, yet evidence supporting their efficacy remains limited. Specific microorganisms, such as Escherichia coli, are displaying increased resilience, underscoring the necessity for prudent antibiotic utilization and investigation of substitutes. Recent metagenomic studies examining ancient DNA from permafrost sediments reveal the natural occurrence of antibiotic resistance genes predating modern antibiotic use. This discovery challenges the notion that resistance is solely a modern phenomenon driven by antibiotic pressures. Bacterial pathogens pose a significant public health threat, with multidrug-resistant organisms emerging in healthcare and community settings. Improper antibiotic use exacerbates environmental contamination and fosters drug-resistant strains, posing threats to human health. Electrochemical sensors offer promising avenues for detecting antibiotic contamination, with advancements enhancing sensitivity. Urgent endeavors are needed to develop novel antimicrobial agents or alternative therapies to combat multidrug-resistant bacteria. This review explores the evolution of resistant bacteria, elucidating mechanisms and potential avenues for prevention and treatment.
Keywords: Challenges; Resistance; discovery; innovations; pathogens